Solutions Architect's Handbook : Kick-start your solutions architect career by learning architecture design principles and strategies /: Kick-start your solutions architect career by learning architecture design principles and strategies. (2020) - Shrivastava, Saurabh; Srivastav, Neelanjali
No abstract available